The Zurich case study of UrbanSim - Patrick Schirmer; Christof Zöllig; Kirill Müller; Balz Bodenmann; Kay Axhausen (European Regional Science Association (ERSA), 2011)
UrbanSim is an open-source software being developed by Waddell and colleagues(Waddell and Ulfarsson, 2004), simulating land use-development in cities based on the choices of households, businesses, land owners and developers, interacting in urban Real Estate markets and with the option to be connected to a transportation simulation. SustainCity is an EU-funded project with twelve European research-institutions1, coordinated by the IVT of the Swiss Federal Institute of Technology Zurich (ETHZ). Within the project of SustainCity2, UrbanSim is being adapted to European conditions by creation of a European version (UrbanSimE) with new calibration of choice-models and additional models for households, demographics and firmographics. Focus will be on the data-structure in Europe as well as the different behaviour of companies, residents and developers. For this UrbanSim will be used in three case studies: Brussels, Paris and Zurich. Although previous studies have been implemented in all of those region, the previous study in Zurich can be considered as a new set up as it uses another version of UrbanSim. This paper will report on the implementation of this parcel-based version of UrbanSim within the Zurich case study of SustainCity. It will refer to the data acquired and necessary as basis for the simulation, discuss the approach of data preparation through PostGIS and report on the new structure of the data-models defined within UrbanSim. Finally the first results of the UrbanSim runs of the Zurich case study will be presented and compared to the runs of previous versions.
Keywords: 330; UrbanSim; Urban Simulation; SustainCity; Zurich case study